Rational Design of Cost-Effective Metal-Doped ZrO2 for Oxygen Evolution Reaction - Zhang, Yuefeng; Wang, Tianyi; Mei, Liang; Yang, Ruijie; Guo, Weiwei; Li, Hao (Nano-Micro Letters, 2024)
The design of cost-effective electrocatalysts is an open challenging for oxygen evolution reaction (OER) due to the “stable-or-active” dilemma. Zirconium dioxide (ZrO2), a versatile and low-cost material that can be stable under OER operating conditions, exhibits inherently poor OER activity from experimental observations. Herein, we doped a series of metal elements to regulate the ZrO2 catalytic activity in OER via spin-polarized density functional theory calculations with van der Waals interactions. Microkinetic modeling as a function of the OER activity descriptor (GO*-GHO*) displays that 16 metal dopants enable to enhance OER activities over a thermodynamically stable ZrO2 surface, among which Fe and Rh (in the form of single-atom dopant) reach the volcano peak (i.e. the optimal activity of OER under the potential of interest), indicating excellent OER performance. Free energy diagram calculations, density of states, and ab initio molecular dynamics simulations further showed that Fe and Rh are the effective dopants for ZrO2, leading to low OER overpotential, high conductivity, and good stability. Considering cost-effectiveness, single-atom Fe doped ZrO2 emerged as the most promising catalyst for OER. This finding offers a valuable perspective and reference for experimental researchers to design cost-effective catalysts for the industrial-scale OER production. Highlights: 1 Surface energy and surface Pourbaix diagram reveal that ZrO2 (111) is the most thermodynamically stable facet and is preferentially occupied by HO* at the equilibrium potential of oxygen evolution reaction (OER). 2 Microkinetic modeling analyzed the OER activity of 40 single-metal doped ZrO2 and identified 16 metals exhibit improved catalytic activity, with Rh and Fe dopants showing the remarkable improvement. 3 Thermodynamic free energy diagrams, density of states analysis, and ab initio molecular dynamics simulations further confirm that Fe–ZrO2 and Rh–ZrO2 are highly promising catalysts for OER, showcasing low ΔG for the rate-determining step, high conductivity, and exceptional stability.